Review on Plant-Based Management in Combating Antimicrobial Resistance - Mechanistic Perspective - Arip, Masita; Selvaraja, Malarvili; R, Mogana; Tan, Lee Fang; Leong, Mun Yee; Tan, Puay Luan; Yap, Vi Lien; Chinnapan, Sasikala; Tat, Ng Chin; Abdullah, Maha; K, Dharmendra; Jubair, Najwan (Frontiers in Pharmacology, 2022)
Antimicrobial resistance (AMR) occurs when microbes no longer respond to any pharmacological agents, rendering the conventional antimicrobial agents ineffective. AMR has been classified as one of the top 10 life-threatening global health problems needed multilevel attention and global cooperation to attain the Sustainable Development Goals (SDGs) according to the World Health Organization (WHO), making the discovery of a new and effective antimicrobial agent a priority. The recommended treatments for drug-resistant microbes are available but limited. Furthermore, the transformation of microbes over time increases the risk of developing drug resistance. Hence, plant metabolites such as terpenes, phenolic compounds and alkaloids are widely studied due to their antibacterial, antiviral, antifungal and antiparasitic effects. Plant-derived antimicrobials are preferred due to their desirable efficacy and safety profile. Plant metabolites work by targeting microbial cell membranes, interfering with the synthesis of microbial DNA/RNA/enzymes and disrupting quorum sensing and efflux pump expression. They also work synergistically with conventional antibiotics to enhance antimicrobial effects. Accordingly, this review aims to identify currently available pharmacological therapies against microbes and AMR, as well as to discuss the importance of plant and secondary metabolites as a possible solution for AMR together with their mechanisms of action. All the information was obtained from government databases, WHO websites, PubMed, Springer, Google Scholar and Science Direct. Based on the information obtained, AMR is regarded as a significant warning to global healthcare. Plant derivatives such as secondary metabolites may be considered as potential therapeutic targets to mitigate the non-ending AMR.